Pas-caerte van Terra Nova, Nova Francia, Nieuw Engeland en de gröte Rivier van Canada - Loon, J. van, ca. 1611-1686 (Amsterdam, 1668)
Hand coloured. Two compass roses. Decorative title cartouche. Bar scales in Derman, Spanish, French and English miles. "Ionnes van Loon, plaet-snyder en zee-caert maker, en Johan Janssonius van Waesberge, excud." (title cartouche). "47" (lower right corner).